Examining the dynamics of the interaction between the development of creative industries and urban spatial structure by agent-based modelling: A case study of Nanjing, China. (April 2018) - Liu, Helin; Silva, Elisabete
Much of the focus of research on creative industries' influence upon urban land use has been around the investment in specific regeneration projects or flagship developments rather than addressing the nature and location of the infrastructure, networks and agents engaged. In other words, the complexity of the institutional/temporal and spatial interaction among the involved elements is overlooked or not well understood. This paper presents an agent-based model named CID-USST (Creative Industries Development-Urban Spatial Structure Transformation) that examines the dynamics of the interaction between the development of creative industries and urban spatial structure by outputting a set of adaptive scenarios through time and space. It reveals that the spatial distribution of both the creative firms and the creative workers evolves in a repeating up-and-down pattern even when the exogenous urban economic condition is set to be steady. Moreover, the analysis also points to the policy implication that more open job/rent market information will lead to more rapid geographical clustering of the creative firms and the creative workers, which possibly may reduce the time cost in their spatial evolvement, and perhaps accelerate innovation if we accept that geographical proximity can enhance knowledge and information spill-over.